Trusted Transcript Management System Using Blockchain - Muhammad Irshad Ishak,; Nur Ziadah Harun, (Applied Information Technology And Computer Science, 2023)
Transcript Management System is a document management system that records student transcripts for the institution. In education, a transcript is a certified record of a student throughout study having entire enrollment history including all courses attempted, grades earned and degree. Counterfeit and forged transcripts can be a significant problem in the job market, causing difficulties for educational institutions, employers, and students. A Trusted Transcript Management System using Blockchain (TTMSB) is a system purpose for this problem by securely storing and verifying educational transcripts. TTMSB uses blockchain technology to create an immutable record of a student's academic achievements, improving the efficiency and security of transcript management. By using blockchain technology, TTMSB can increase traceability, improve performance and speed in the management process, and make it easier to spot and verify fake transcripts.